Evaluating EQ in Opium Addicts Visiting the Rehabilitation Centers of Rafsanjan University of Medical Sciences - Ali Asghar Ranjbar Totoei; Narges Khanjani; Mohammad Reza Mirzabeigi (پژوهش‌های سلامت‌محور, 2016)
Evaluating EQ in Opium Addicts Visiting the Rehabilitation Centers of Rafsanjan University of Medical Sciences